Determination of pteridines in biological samples with an emphasis on their stability - Tomšíková, H; Tomšík, P; Solich, P; Nováková, L (Bioanalysis, 2013)
Pteridines are a group of endogenous heterocyclic compounds whose concentrations in biological fluids may be increased in some disorders, such as infections, autoimmune disorders and cancer. In particular, pteridine concentrations in urine may represent promising noninvasive markers. However, their specificity requires further investigation. Pteridines can occur in three oxidation states with different stability. In order to enable the analysis of the unstable di- and tetra-hydroforms either an oxidation (mainly with iodine) or stabilization by reducing agents is applied. Due to the high polarity of pteridines, many analytical procedures employed ion-pair, ion-exchange or hydrophilic interaction liquid chromatography using mostly fluorescence detection. In the last decade, MS was found to be applicable. The objective of this Review is to show possibilities and different approaches in pteridine analysis in biological samples.
Keywords: tělesné tekutiny; Temperature; Chromatography, Liquid; Body Fluids; fluorescenční spektrometrie; molekulární struktura; Molecular Structure; Pteridines; Hydrogen-Ion Concentration; Mass Spectrometry; chromatografie kapalinová; koncentrace vodíkových iontů; oxidace-redukce; lidé; pteridiny; Humans; hmotnostní spektrometrie; teplota; Spectrometry, Fluorescence; Oxidation-Reduction